(untitled) (Journal of Comparative & International Higher Education, 2021)
Both internationalization of higher education and use of English as a global language (EGL) coexist, for the latter is a vital tool to attain the former and vice versa. Although the former came into existence in non-native English-speaking countries in Europe, and the latter became the major medium of instruction at universities with the de facto ‘extraterritorial’ lingua franca, research into international students’ issues has mainly been conducted in English-speaking countries. This paper, therefore, aims to explore such value and use of EGL in a higher education internationalization context in Bulgaria. With the qualitative research approach, two themes emerge, answering two research questions. The results collected from 13 students from European and former Soviet backgrounds offer insights into linguistic, cultural, and psychological challenges international students tend to encounter as well as determinants that impact their adjustment.